2002
DOI: 10.1364/ao.41.001500
|View full text |Cite
|
Sign up to set email alerts
|

Color image recognition by use of a joint transform correlator of three liquid-crystal televisions

Abstract: We present a joint transform correlator for color image recognition by using three liquid-crystal spatial light modulators. A method for simultaneously obtaining the correlation peaks of red, green, and blue is proposed and experimentally demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
(7 reference statements)
0
3
0
1
Order By: Relevance
“…并且随着空间光调制器性能的愈加稳定, 人们可以 摆脱全息法制作匹配滤波器的非实时识别, 采用光电 混合型实现准实时识别. 除了实时性的追求以外, 人 们还实现了对复杂图像识别, 比如人脸 [43][44][45][46] 、DNA序 列 [47] 、虹膜 [48] 等生物信息用于安全系统的识别以及三 维 [49][50][51][52] 、彩色物体 [53][54][55][56] 等其他维度的复杂识别. 最近 JTC的概念还被应用于编码解码领域 [57][58][59] .…”
Section: 在光学相关识别的历史进程中 人们从非实时处unclassified
“…并且随着空间光调制器性能的愈加稳定, 人们可以 摆脱全息法制作匹配滤波器的非实时识别, 采用光电 混合型实现准实时识别. 除了实时性的追求以外, 人 们还实现了对复杂图像识别, 比如人脸 [43][44][45][46] 、DNA序 列 [47] 、虹膜 [48] 等生物信息用于安全系统的识别以及三 维 [49][50][51][52] 、彩色物体 [53][54][55][56] 等其他维度的复杂识别. 最近 JTC的概念还被应用于编码解码领域 [57][58][59] .…”
Section: 在光学相关识别的历史进程中 人们从非实时处unclassified
“…The data is parallelised but it is still effectively treating each colour as a separate correlation and combining the correlation plane results. Colour JTC have been shown by Yu et al [2] and Hsieh et al [3], quaternion and hyper-complex Clifford algebras have been successfully demonstrated for colour manipulation [4], image registration [5] and correlation [6] [7] [8] but since the data remains three dimensional, they are physically more difficult to realise in an optical system and when implemented on a computer they often involve multiple FFTs of the data, making them slow. This paper demonstrates a simple way of encoding colour information that can be implemented on a spatial light modulator or via a high speed FFT operation on an electronic processor.…”
Section: Introductionmentioning
confidence: 99%
“…The application of optical correlation for color pattern recognition has been reported in some papers [8][9][10][11][12][13][14][15]. Out of the several schemes proposed so far, multichannel correlation is most widely used.…”
Section: Introductionmentioning
confidence: 99%